Strategies for managing major diseases in Asian seabass aquaculture - Gen Hua Yue; Changjun Guo (2025)
Abstract Asian seabass (Lates calcarifer ) is becoming an important species for aquaculture. However, the Asian seabass aquaculture industry faces a significant challenge of disease outbreaks that can jeopardize fish health and production. This review delves into the major diseases affecting Asian seabass aquaculture and explores their causes, symptoms, and management approaches. We focused on the key pathogens responsible for these outbreaks, the environmental factors contributing to disease susceptibility, and the latest advancements in disease prevention and management. By addressing these critical aspects, this review addresses the needs of aquaculturists, researchers, and policymakers with the knowledge required to promote resilient and sustainable Asian seabass farming. We aim to shed light on the challenges posed by disease while highlighting innovative strategies that offer promise for the future of this thriving industry. This comprehensive examination serves as a valuable resource for those invested in ensuring the health and vitality of Asian seabass, securing a consistent supply to meet the demands of global seafood markets.